Asset securitization for small and medium-sized real estate enterprises in China - Wang Shuangzhi (2022)
Based on the economic background of strict regulation and control of real estate bank credit and on the background of vigorous development of the financial system of direct financing in China, this thesis analyzes the necessity and feasibility of asset securitization financing for small and medium-sized real estate cmpanies. It shows that this type of financing is not only in line with the direction of the dual economic and financial reforms, but also that small and medium-sized real estate companies can meet their financing needs by relying on their specific high-quality assets rather than the main body credit financing. Using Company A as a typical case, we carried out design of the securitization program for the underlying asset pool construction, choice of bankruptcy remote and credit enhancement instruments, and product tranches, based on the characteristics of the asset composition status and low credit rating of the main body. Not only does it meet financing needs, but it also improves other financial situations. Therefore, this thesis has reference value, promotion, and practical significance for small and medium-sized real estate companies.